Ethical and Methodological Dilemmas in Ethnographic Research among the Far Right - Kotonen, Tommi; Mustamo, Aila (The Finnish Anthropological Society, 2026)
This essay belongs to the essay series ‘The Anthropologist’s Toolkit: Reflections on Ethnographic Methodology’. In this series, authors peer into the anthropologist’s toolkit to reflect on what ethnographic methodology constitutes in all its multimodal forms.
In this essay, we ask how an ethically sustainable ethnography of the Far Right can be conducted, bearing in mind the risk of normalising both extreme ideologies and the points of view of participants. Abandoning ethnographic methodology in research among the Far Right is also an ethical choice with consequences. Based on our own fieldwork experiences and on previous studies, we reflect on the key ethical dilemmas we have encountered when studying the Far Right. Beyond specific issues arising when contacting and meeting research participants, the concepts used and the language in general also matter.